ACLS case clips - MosbyJems (Firm) (St. Louis : MosbyJems, 2003)
A collection of brief clips of actual patients in emergency situations, designed to illustrate advanced cardiac life support instruction
VHS
Keywords: Advanced Cardiac Life Support